Education of Diarrhea in Toddlers Treatment for Moms in Kalisat Village, Jember Regency: Edukasi Penanganan Diare pada Balita kepada Ibu-Ibu di Desa Kalisat, Kabupaten Jember - Dyan Maulani; Rizka Yolanda Febiocti; Faiza Ilma Zazila; Muhammad Abu Bakar; Yunita Andesia Putri Artika (KHD Production, 2024)
Diarrhea is an environmental disease that is the main cause of morbidity and death. Diarrhea is a digestive canal infection that is a health problem in the world, including Indonesia. The percentage of toddler deaths due to diarrhea in Indonesia is quite high, namely around 4.55%. Health education about treating diarrhea is one way to reduce the incidence of diarrhea in the community. This activity aims are to provide knowledge about the causes of diarrhea, its symptoms, how to treat it, and preventive measures in Kalisat Village, Jember Regency. The method is to educate mothers of the Posyandu in Kalisat Village. The results of the activity showed active participation in the material presented and succeeded in bridging public health knowledge. It is hoped that this activity can continue and have a positive impact on the health of the people of Kalisat Village in the future, preventing cases of toddler deaths caused by diarrhea.